Promoting end-of-season product through online channel in an uncertain market - Chen, Pingping; Zhao, Ruiqing; Yan, Yingchen; Zhou, Chi (European journal of operational research, 2021)
•Firm’s end-of-season product promotion through online channel is presented.•Equilibrium online channel format between agency selling and reselling is obtained.•Effects of promotional pricing timing and uncertain demand are investigated.•Promotional pricing timing affects firm’s decisions only in reselling format.•Agency selling format is no longer profitable under certain conditions. Firms typically introduce online promotional channels based on the cooperative format of agency selling or reselling to promote end-of-season products. The selection of the agency selling or reselling format is greatly affected by a firm’s pricing timing between traditional and online promotional channels, particularly in an uncertain market. Within this context, we examine how the pricing timings in an online promotional channel relative to a traditional channel impact a firm’s selection between agency selling and reselling formats in an uncertain market. We find that the promotional pricing timings have no effect on the firm’s price decisions under the agency selling format, whereas they might lead to downward prices under the reselling format—even lower than those under the agency selling format. We show that considering promotional pricing timing in an uncertain market fundamentally changes the general intuition that the firm prefers the agency selling to reselling format due to the double-marginalization effect. Specifically, the reselling format might be more profitable for the firm when it sets traditional-channel promotional price prior to introducing the online promotional channel in an optimistic market (i.e., a market more likely to have high demand) or adopts the opposite promotional pricing timing of channels in a pessimistic market (i.e., a market more likely to have low demand). Our findings complement the emerging online retail literature by underscoring the interacting forces of promotional pricing timing and uncertain demand on a firm’s reselling versus agency selling format choice in promoting end-of-season product online.